Variations on primary metabolites of the carrageenan-producing red algae Sarcopeltis skottsbergii from Chile and Sarcopeltis antarctica from Antarctic Peninsula - Pasqualetti, Cesar B.; Carvalho, Maria Angela M.; Mansilla, Andres; Avila, Marcela; Colepicolo, Pio; Yokoya, Nair S. (Frontiers in Marine Science, 2023)
Several studies reported that gametophytes and tetrasporophytes of Gigartinaceae produce different carrageenan types, as observed in Sarcopeltis species although they have isomorphic haploid and diploid phases. Cystocarpic and non-fertile plants of Sarcopeltis (ex Gigartina) skottsbergii produced kappa-carrageenans, while tetrasporophytes produced lambda-carrageenans, and yields were higher in cystocarpic and sterile specimens than in tetrasporophytes. However, comparison on the other primary metabolites among different life history phases still needed to be investigated. Then, we tested the hypothesis if the variation on primary metabolites (pigments, proteins and carbohydrates) are related to the life history phases of Sarcopeltis antarctica and Sarcopeltis skottsbergii, and/or are influenced by abiotic factors. Primary metabolites of S. antarctica varied according to the life-history phases: non-fertile specimens presented higher phycobiliprotein concentrations, tetrasporophytes presented higher chlorophyll a concentrations, and cystocarpic specimens presented higher concentrations of proteins, polysaccharides and floridean starch. However, primary metabolites of S. skottsbergii varied in response to some abiotic factors (nutrients, temperature and salinity), since principal component analysis evidenced two groups; one was related by the higher nitrate and phosphate concentrations, and the other was related to the higher temperatures and lower salinities. Concentrations of floridean starch, low molecular weight carbohydrates, and polysaccharides are higher in S. antarctica than in S. skottsbergii, which could be related to the protective role of these compounds against salinity variation and low temperatures faced in the Antarctic extreme environments.